Impact of plasma-wall interaction and exhaust on the EU-DEMO design. (March 2021) - Maviglia, F.; Siccinio, M.; Bachmann, C.; Biel, W.; Cavedon, M.; Fable, E.; Federici, G.; Firdaouss, M.; Gerardin, J.; Hauer, V.; Ivanova-Stanik, I.; Janky, F.; et al.
Highlights: The EU-DEMO PFC protection strategy exhibits common features with ITER, but also some important differences. EU-DEMO foresees the presence of limiters, to protect the thin breeding wall during flat-top, planned and unplanned transients. EU-DEMO is currently designed with an ITER-like LSN divertor but recurring to divertor sweeping as an emergency manoeuvre by reattachment. The adoption of ELM-free regimes may in the future lead to significant modifications in the plant design. First phases of the EU-DEMO design have shown that PFC protection is and must be driven by transients rather than by the stationary flat-top phase. Abstract: In the present work, the role of plasma facing components protection in driving the EU-DEMO design will be reviewed, focusing on steady-state and, especially, on transients. This work encompasses both the first wall (FW) as well as the divertor. In fact, while the ITER divertor heat removal technology has been adopted, the ITER FW concept has been shown in the past years to be inadequate for EU-DEMO. This is due to the higher foreseen irradiation damage level, which requires structural materials (like Eurofer) able to withstand more than 5 dpa of neutron damage. This solution, however, limits the tolerable steady-state heat flux to ~1 MW/m 2, i.e. a factor 3–4 below the ITER specifications. For this reason, poloidally and toroidally discontinuous protection limiters are implemented in EU-DEMO. Their role consists in reducing the heat load on the FW due to charged particles, during steady state and, more importantly, during planned and off-normal plasma transients. Concerning the divertor configuration, EU-DEMO currently assumes an ITER-like, lower single null (LSN) divertor, with seeded impurities for the dissipation of the power. However, this concept has been shown by numerous simulations in the past years to be marginal during steady-state (where a detached divertor is necessary to maintain the heat flux below the technological limit and to avoid excessive erosion) and unable to withstand some relevant transients, such as large ELMs and accidental loss of detachment. Various concepts, deviating from the ITER design, are currently under investigation to mitigate such risks, for example in-vessel coils for strike point sweeping in case of reattachment, as well as alternative divertor configurations. Finally, a broader discussion on the impact of divertor protection on the overall machine design is presented.